Review of the Campaign to Prevent Falls in Construction - O’Donnell, Kevin (Frontiers in Public Health, 2017)
Roofing is one of the most dangerous activities in the construction industry according to the US Bureau of Labor Statistics. Although injuries are manifold in this industry element, the vast majority of them occur as a result of falls from elevation (1, 2). These events lead to physical injury, fatalities, and financial burdens to the individual injured, their families, the employer, and the construction market as a whole (3, 4). In order to reduce construction worker falls, Occupational Health and Safety Administration launched the nationwide Campaign to Prevent Falls in Construction on April 26, 2012 (5). The campaign applied several learning theories that are utilized and proven effective in public health interventions. However, the initiative fails to address a key subpopulation. Further critical assessment of this campaign is now needed to evaluate overall effectiveness.